Inovasi Produk Limbah Kain Perca Berbasis Green Behavior Pada Warga Rejosari Pakal Surabaya - Wiwik Handayani; Sri Suryani Yuprapti Winasih; Zumrotul Fitriyah; Septi Ayu Dianty; Ari Setya Budi; Hasto Hidayatullah (LP3M STAI Darussalam Krempyang Nganjuk, 2022)
The purpose of this community service is to provide assistance to low-income communities by utilizing patchwork into innovative products and being able to market products in the marketplace. The target audience, namely residents of RW 3, Benowo sub-district, Pakal sub-district, Surabaya. The method used is participatory and intensive assistance in the form of activities: 1) training on making products from patchwork; 2) training on how to make product designs; 3) Digital marketing training through social media platforms. The results of the dedication are able increase the income of the poor and form green behavior. In particular, this program has been able to provide knowledge on the manufacture of innovative products made from patchwork; Designing products from patchwork; and product marketing skills on the market place at the UKM Jurang Kuping Kreatif Pakal Surabaya.